Communications on pure and applied mathematics - New York University Institute for Mathematics and Mechanics; New York University. Institute of Mathematical Sciences; Courant Institute of Mathematical Sciences (New York John Wiley, 1948)
Access available online from 1996-
Title from cover.
Subtitle varies.
Keywords: Mathematics -- Periodicals; Mechanics -- Periodicals